Battle group on alert in the gulf world tragedy - Makin, Anthony; Wolfinger, Kirk; Battle Group Production ([United States] : Battle Group Production, 1998)
This program is about the preparation made by US battle group in facing a war. Focus on their preparation to against enemy and to get the target
Executive producer, Ultan Guilfoyle ; editor, Elizabeth Ackerman
Narrator: William Baldwin
VCD format
Subtitle in Chinese
Keywords: Armed Forces